Rural development statistics 1993-94 - National Instute of Rural Development (Hyderabad, 1995)
The current issue, tenth in the series, is a compendium of selected statistical tables relating to the various facets of rural development highlighting the levels and changes taking place overtime. In the current issue a new section has been added dealing with social consumption based on the 42nd round data of National Sample Survey and 1991 Population Census. Further, a sub-section on "Wasteland Development and Afforestation" is added in section - 3. The reference years for most of the data included in this publication are 1992-93 and 1993-94. In all 242 tables spanning over 13 sections are included in the current volume. A note highlighting the trends and significant aspects of the tables included under each section has been provided at the beginning of each section.
Keywords: Statistics India 1983 94